1999
DOI: 10.1021/jp983821n
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactivity and Excited-State Density Functional Theory

Abstract: Softness and polarizability are calculated for different complexions of two-state ensembles of various helium isoelectronic systems (He, Li+, Be2+, B3+, C4+). It is shown for the first time for the systems studied that an increase in the excited-state contribution in a two-state ensemble makes the system softer and more polarizable, as expected from the principles of maximum hardness and minimum polarizability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 40 publications
3
70
0
1
Order By: Relevance
“…However, DFT has recently witnessed a great progress in its conceptual branch [33]. It tackles the problem of chemical reactivity by employing a perturbative approach, similar to experimental thermodynamics [34]. A lot of properties known from experimental chemistry, such as chemical potential, electronegativity, polarizability or hardness and softness, can be given strict definitions on the ground of conceptual DFT.…”
Section: Introductionmentioning
confidence: 99%
“…However, DFT has recently witnessed a great progress in its conceptual branch [33]. It tackles the problem of chemical reactivity by employing a perturbative approach, similar to experimental thermodynamics [34]. A lot of properties known from experimental chemistry, such as chemical potential, electronegativity, polarizability or hardness and softness, can be given strict definitions on the ground of conceptual DFT.…”
Section: Introductionmentioning
confidence: 99%
“…14 This principle states that the natural direction of evolution of any system is towards a state of minimum polarizability. Both principles have been applied successfully to the study of molecular vibrations, 9,15-18 internal rotations, 6͑b͒,19 excited states, 20,21 aromaticity, 22 and different types of chemical reactions. 12,[23][24][25][26][27][28][29][30][31][32][33] It has been found in most of these cases that the conditions of maximum hardness and minimum polarizability complement the minimum energy criterion for molecular stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, relaxation of these constraints seems to be permissible, and in particular, it has been found that in most cases the MHP still holds even though the chemical and external potentials vary during the molecular vibration, internal rotation or along the reaction coordinate. 12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Hereafter, we will refer to the generalized MHP ͑GMHP͒ or MPP ͑GMPP͒ as the maximum hardness or minimum polarizability principles that do not require the constancy of chemical and external potentials during molecular change. It is worth emphasizing that the generalized versions of these principles have not been proven.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the benzene ring in the molecule achieves an aromatic π-sextet [16]. This modification in the structural geometry will give the required stability for the structure by allowing the atoms in the molecule to achieve a stable octet.…”
Section: Scheme (2) Exhibits the Transition State The Product Of Thementioning
confidence: 99%